Small animal patient preoperative preparation: a review of common antiseptics, comparison studies, and resistance - Nye, Alicia K.; Thieman Mankin, Kelley M. (Frontiers in Veterinary Science, 2024)
This review aims to describe commonly used antiseptics in veterinary medicine including their mechanism of action, spectrum of activity, potential adverse effects, and application techniques.Additionally, it provides a review of the veterinary literature comparing antiseptics, a discussion of effectiveness and efficacy studies, and the potential for increased resistance to biocides and antimicrobials. This review concludes that appropriate selection and use is necessary to prevent the occurrence of surgical site infections, adverse effects, and potential for increasing resistance to antimicrobials. Continued research is needed to fill gaps in the current knowledge such as optimal preparation procedures for various surgical sites, standardization of efficacy and effectiveness testing, and the clinical impact of decreased susceptibility to chlorhexidine and other antiseptics.